Preclinical Evaluation of Botulinum Toxin Type E (TrenibotulinumtoxinE) Using the Mouse Digit Abduction Score (DAS) Assay - Gregory S. Nicholson; David Canty; Annemarie Southern; Kevin Whelan; Amy D. Brideau-Andersen; Ron S. Broide (Toxins)
TrenibotulinumtoxinE (trenibotE), a botulinum neurotoxin serotype E (BoNT/E), is being developed for clinical use, and can fill a unique treatment gap for patients who are seeking neurotoxin treatment with a rapid onset and short duration of effect. This preclinical study characterized the pharmacological activity of trenibotE using the mouse Digit Abduction Score (DAS) assay. A comparative analysis was also performed between trenibotE and an equi-efficacious dose of the botulinum neurotoxin serotype A (BoNT/A) onabotulinumtoxinA (onabotA). TrenibotE showed a dose-dependent increase in peak DAS and duration of effect. A comparison of onabotA and trenibotE in this assay at approximate equi-efficacious doses showed trenibotE to have a faster onset of effect (trenibotE yielded a significantly greater effect as early as 6 h post-injection), shorter time to peak effect (24–27 h vs. 2 days), and an overall shorter duration of response (3 days vs. 14 days). The unique temporal characteristics of trenibotE and pharmacological differentiation from onabotA observed in this preclinical assay support the clinical development of this molecule.